2017
DOI: 10.1007/s12011-017-1074-3
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Assessment of Titanium Dioxide Nanoparticles (TiO2-NPs) Induced Hepatotoxicity and Ameliorative Effects of Cinnamomum cassia in Sprague-Dawley Rats

Abstract: This study assessed the protective effects of Cinnamomum cassia (cinnamon) bark extract in rats exposed to titanium dioxide nanoparticles or titanium dioxide bulk salt. For in vivo evaluation of the ameliorative role of the cinnamon extract, the experimental groups were orally administered with the cinnamon extract at different dose levels (50 or 100 or 150 mg/kg bodyweight) along with the subcutaneous injections of 150 mg/kg bodyweight titanium dioxide nanoparticles or titanium dioxide bulk salt. The extract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 58 publications
(56 reference statements)
2
16
0
Order By: Relevance
“…These results are in line with those observed by Bermudez et al Shakeel et al (2017). They found that TiO2 NPs decreased body weight in the experimental animals.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in line with those observed by Bermudez et al Shakeel et al (2017). They found that TiO2 NPs decreased body weight in the experimental animals.…”
Section: Discussionsupporting
confidence: 93%
“…The first two of the above species belong to the most widely manufactured and used nanomaterials [ 19 ] This explains why they are frequently subjected to toxicological assessment, though in vitro as a rule, and much less often in short-term animal experiments. The scientific literature of this kind dealing with TiO 2 -NP toxicity may be exemplified by [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], and that on SiO 2 -NP toxicity by [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ] and numerous other sources. Apart from several studies performed on unicellular algae or plant cells, the toxicity of Al 2 O 3 -NPs had been investigated much less, even on cell cultures [ 48 , 49 , 50 ], and only one of the latter [ 50 ] also involved the administration of a single oral dose to mice.…”
Section: Introductionmentioning
confidence: 99%
“…As reported in titanium dioxide (TiO 2 )‐NPs, mice and rat models showed a rise in ROS and decreased expression of superoxide dismutase and GPx, alteration in mRNA and cytoplasmic proteins and significant expression in CYP1A resulting in liver damage and oxidative injury (Shakeel et al, ; Shrivastava, Raza, Yadav, Kushwaha, & Flora, ). Increase in liver weight and its enzymes namely, ALT, AST and LDH is also evident in TiO 2 ‐NP toxicity, in addition to significant alterations in cytokines (Alarifi et al, ; Cui et al, ; Morgan, Ibrahim, Galal, Ogaly, & Abd‐Elsalam, ).…”
Section: Means Of Chemical Modulation Of Hepatic Apoptosismentioning
confidence: 83%